2000
DOI: 10.1103/physrevb.62.5079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of random well-width fluctuations on the exciton optical absorption spectrum in single quantum wells

Abstract: The optical density function is calculated in a single quantum well for two-dimensional excitons moving in a random potential in the interfacial plane generated by fluctuations of the quantum-well thickness. Assuming Gaussian statistics for the random potential distribution, we have applied the path-integral approach and obtained in the adiabatic approximation two asymptotic analytical expressions for the low-and high-energy tails of the optical absorption spectrum. The high-energy tail of the exciton absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As known from other groups [32,33], using a comparable approach to describe the interface roughness of quantum wells, one has to distinguish between islands larger than the exciton Bohr radius, separated by monolayer steps, and much smaller areas with a certain microroughness, so that the exciton rather sees rapid fluctuations than monolayer steps of c=2 [34]. In the first case we would expect a splitting of the exciton luminescence.…”
Section: Resultsmentioning
confidence: 97%
“…As known from other groups [32,33], using a comparable approach to describe the interface roughness of quantum wells, one has to distinguish between islands larger than the exciton Bohr radius, separated by monolayer steps, and much smaller areas with a certain microroughness, so that the exciton rather sees rapid fluctuations than monolayer steps of c=2 [34]. In the first case we would expect a splitting of the exciton luminescence.…”
Section: Resultsmentioning
confidence: 97%
“…With these in mind, it is clear that the absorption properties in low dimensional system are strongly influenced by disorder [33,34,39,[43][44][45][47][48][49]. For instance, Burresi and collaborators [42] provide experimental evidence that 2D disordered photonic architecture applied to a thin film material induces an enhancement in the absorption of the thinfilm solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Bansal et al [34] reported that the interface disorder of AlGaAs/GaAs quantum wells at high magnetic field reduces inhomogeneously broadened photoluminescence linewidth. Sa-yakanit et al [49] reported that the random potential generated by the fluctuations of the quantum-well thickness Al x Ga 1−x As/GaAs/ Al x Ga 1−x As exhibits a monotonic broadening and decrease of the magnitude of the exciton absorption peak with increasing disorder. Other examples in the literature on the effect of disorder on absorption, Banon et al [39] presented a mathematical and computational model able to simulate the optoelectronic response of semiconductor alloys with a compositional disorder.…”
Section: Introductionmentioning
confidence: 99%